Bimbingan Teknis Media Lagu dalam Pendidikan Islam Multikultural untuk Anak Usia Dini - Shofwan, Arif Muzayin; Prawinda, Raras Ayu; Farantika, Dessy; Apriliyanti, Apriliyanti; Hidayah, Firda Roudlatul; Lestariningsih, Lestariningsih; Putra, Fatra Nonggala (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Songs can be used as a learning medium for multicultural Islamic education for early childhood. Learning using songs aligns with the principles of learning through play, playing while learning, and learning while singing while learning, which are certainly very enjoyable for young children. This paper examines community service in the form of technical guidance on songs as a learning medium for multicultural Islamic education for early childhood. Two methods were used in this service: lecture and question-and-answer. The technical guidance on songs as a learning medium proceeded smoothly without any obstacles. This service demonstrates the continuity of the material presented with the introduction to religion in Indonesia for early childhood. Furthermore, it is hoped that this type of community service activity will be conducted more frequently to increase knowledge that can be used in teaching early childhood.